2019
DOI: 10.1002/jsfa.9580
|View full text |Cite
|
Sign up to set email alerts
|

Acacia, cherry and oak wood chips used for a short aging period of rosé wines: effects on general phenolic parameters, volatile composition and sensory profile

Abstract: BACKGROUND There is a restricted knowledge about the potential impact of the use of different wood chip species on the rosé wine aging process. Thus, the aim of this work was to evaluate the general phenolic parameters, aroma composition and sensory profile of rosé wines during a short maturation (20 aging days) in contact with wood chips from oak, acacia and cherry. In addition, the different wood chips were added to a rosé wine without a previous clarification process (unfined wine) and to a rosé wine submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Moreover, other authors [27,30] described an increase of total phenols as a result of wood chip addition during fermentation after two months of contact with the wine. Therefore, the results obtained in our experimental work for all rosé musts and wines confirmed the tendency previously reported by other authors for higher total phenolic content in red [17][18][19][20][21], white [23][24][25], and rosé [15] wines aged in contact with different wood chips.…”
Section: General Phenolic Composition and Color Parameter Changes In supporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, other authors [27,30] described an increase of total phenols as a result of wood chip addition during fermentation after two months of contact with the wine. Therefore, the results obtained in our experimental work for all rosé musts and wines confirmed the tendency previously reported by other authors for higher total phenolic content in red [17][18][19][20][21], white [23][24][25], and rosé [15] wines aged in contact with different wood chips.…”
Section: General Phenolic Composition and Color Parameter Changes In supporting
confidence: 92%
“…These findings could derive from oxidation reactions during aging or from condensation reactions between anthocyanins and certain wood molecules, all of which would generate large, insoluble, and precipitable polymers. In addition, Santos et al [15] reported no differences for color intensity between rosé wines aged in contact with different wood chip species over 20 aging days. Furthermore, several authors point out the aging time as the main factor affecting the physicochemical features of wines aged in contact with wood [19,29].…”
Section: General Phenolic Composition and Color Parameter Changes In mentioning
confidence: 98%
See 2 more Smart Citations
“…Maceration of Carménère wines in Romanian oak chips (Quercus petraea) resulted in higher furfural content (2192.31 μg L -1 ) than wines treated with French (Quercus petraea; 1484.77 μg L -1 ), American (Quercus alba; 1421.67 μg L -1 ) or Colombian oak (Quercus humboldtii; 511.08 μg L -1 ), showing that concentration of furanic compounds can be influenced by the specie/origin of oak due to differences in the levels of furfural precursors such as hemicelluloses (MARTÍNEZ-GIL et al, 2018). The influence of the wood was also confirmed in the aging of rosé wine in contact with four types of wood chips (Robinia pseudoacacia, Prunus avium, Quercus alba, Quercus petraea), being the lowest and highest furfural levels found in wines aged with wood chips of R. pseudoacacia (1350 μg L -1 ) and Q. petraea (2403 μg L -1 ), respectively (SANTOS et al, 2019). Role of wood heating was verified in the greater furfural concentration (2800 μg L -1 ) in Chardonnay wines aged in French oak barrels (95% Quercus petraea and 5% Quercus robur) toasted at 55 °C for 36 min than those reported in wines aged in barrels heated at 52 °C for 36 min (2000 μg L -1 ) or 60 °C for 10 min (2200 μg L -1 ) (GONZÁLEZ- CENTENO et al, 2019).…”
Section: Furfuralmentioning
confidence: 70%